Non‐Steric Interactions Predict the Trend and Steric Interactions the Offset of Protein Stability in Cells. Issue 18 (21st June 2018) - Davis, Caitlin M.; Gruebele, Martin
Abstract: Although biomolecules evolved to function in the cell, most biochemical assays are carried out in vitro . In‐cell studies highlight how steric and non‐steric interactions modulate protein folding and interactions. VlsE and PGK present two extremes of chemical behavior in the cell: the extracellular protein VlsE is destabilized in eukaryotic cells, whereas the cytoplasmic protein PGK is stabilized. VlsE and PGK are benchmarks in a systematic series of solvation environments to distinguish contributions from non‐steric and steric interactions to protein stability, compactness, and folding rate by comparing cell lysate, a crowding agent, ionic buffer and lysate buffer with in‐cell results. As anticipated, crowding stabilizes proteins, causes compaction, and can speed folding. Protein flexibility determines its sensitivity to steric interactions or crowding. Non‐steric interactions alone predict in‐cell stability trends, while crowding provides an offset towards greater stabilization. We suggest that a simple combination of lysis buffer and Ficoll is an effective new in vitro mimic of the intracellular environment on protein folding and stability. Abstract : Interactions inside cells : Cell lysate, crowders, and physiological buffers allow differentiation of crowding and sticking interactions that are important in the cell. Surprisingly, non‐steric interactions alone predict whether a protein is stabilized or destabilized in the cell. A method for mimicking in‐cell steric and non‐steric interactions is proposed.